Skarga potoczna w strukturze narracyjnej - Wyrwas, Katarzyna (Stylistyka, 2021)
In this artice the author presents some remarks on adaptive structure ofspoken complaint. The analyses demonstrate the contamination of complaint and narrative structure. In analysed spoken texts narrative seems to be structurally "stronger" genre because of its structural dominant: narrative scheme, consisting of few e lements arranged in tum (Abstract, Orientation, Evaluation, Result and Coda). However, spoken complaint has also a strong dominant which is semantic dominant - negation showing speaker's attitude to events of his life. The negation exists on text surface or in deep semantic structure of . Analyses presented in this article shows that most complaint elements are located in Orientation and Coda which often contains speaker's opinion about reported events. The opinion in everyday spoken narratives may be positive or negative, and sometimes it can be even humoristic, but in spoken complaint this finał opinion is always negative.